PfEMP1, polymorphism and pathogenesis. - Newbold, C; Craig, A; Kyes, S; Berendt, A; Snow, R; Peshu, N; Marsh, K (1997)
The virulence of Plasmodium falciparum relative to the other species of malarial parasite which infect humans is thought to be due to this parasite's ability to adhere to endothelial cells lining small blood vessels and, in some cases, to its ability to form rosettes with uninfected erythrocytes. The latter phenotype has been found more frequently in cases of severe disease. The former property means that only the younger, asexual, intra-erythrocytic forms circulate whereas the more mature developmental stages are sequestered in the vasculature of a variety of organs. When large numbers of parasites accumulate in a vulnerable target organ such as the brain, the the life-threatening condition of cerebral malaria may result. While the factors that control whether or not cerebral malaria develops are not clearly defined, one crucial determinant my be the endothelial receptors utilised by the infecting isolate. Many such receptors have been identified, including CD36, thrombospondin, ICAM-1, VCAM, E-selectin and chondroitin-4-sulphate. The results of laboratory, field, post-mortem and direct receptor-binding studies indicate that, of the receptors currently identified, ICAM-1 binding is more likely to be associated with the development of cerebral malaria. The molecule expressed on the surface of the infected erythrocyte which mediates adherence to endothelium belongs to a large family of clonally variable antigens encoded by the var genes. The evidence for this conclusion and progress in defining the regions of var-gene products responsible to receptor-specific binding are discussed. Finally, the organization of the var genes within and between parasites is discussed in relation to the evolution of the var-gene family and its functions of antigenic variation and endothelial adhesion.